If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -2(y + -2) + 5 = 0 Reorder the terms: 4y + -2(-2 + y) + 5 = 0 4y + (-2 * -2 + y * -2) + 5 = 0 4y + (4 + -2y) + 5 = 0 Reorder the terms: 4 + 5 + 4y + -2y = 0 Combine like terms: 4 + 5 = 9 9 + 4y + -2y = 0 Combine like terms: 4y + -2y = 2y 9 + 2y = 0 Solving 9 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 2y = 0 + -9 2y = 0 + -9 Combine like terms: 0 + -9 = -9 2y = -9 Divide each side by '2'. y = -4.5 Simplifying y = -4.5
| 4x+18=3+8x-5 | | |-6|-|10-3|= | | 1/2+(-5/8) | | 2x+9=-97-10x | | 2/3p+1=-7 | | 5-2x+x=-10 | | 2/3+1=-7 | | -6(8m+7)= | | 7675483920129834765434x=5 | | 11-7x=59-28x | | -4x-12=-16-3x | | x^2+8x=4x | | -4x+20=-16+5x | | x/4=-3-(-7) | | -4x-7=9x+32 | | 4x+7x=2x-8 | | p=80-2qinversa | | 0.75(2x+3)-3.5=0.8(1-x) | | -5-2x+x=-10 | | a^2+a-1=o | | x=6(3.12)y | | y=6(3.12)x | | -4x-20=-16-5x | | 5+4x-x=20 | | 4x+12=16+3x | | 28c^5-8c^9= | | -3+4x-x=6 | | -6g+7g-7= | | b^2+12=0 | | 4x+4k=2x+14k | | 24/24 | | 10x+28=3x+147 |